Odpowiedzi

Najlepsza Odpowiedź!
2009-11-25T20:16:15+01:00
(√3 - √5 + √3 + √5)² =
[√3 -√5) + √(3+√5)]² =
= 3 - √5 +2√(3-√5)*√(3+√5 )+ 3 + √5=
= 6 + 2√(3-√5)(3+√5) =
= 6 + 2√[3²-(√5)²] =
= 6 + 2√( 9-5) =
= 6 + 2√4=
= 6 +2*2=
= 6 +4 =
=10


√(3-√5) wyrażenie w nawiasie jest pod pierwiastkiem
√(3+√5 ) wyrażenie w nawiasie jest pod pierwiastkiem
√[3²-(√5)²] wyrazenie w nawiasie [ ] jest pod pierwiastkiem
2009-11-25T20:18:38+01:00
(√(3 - √5) + √(3 + √5))²=3-√5+2√[(3-√5)(3+√5)]+3+√5=
=6+2√(9-5)=6+2√4=6+4=10